2013
DOI: 10.1371/journal.pone.0077828
|View full text |Cite
|
Sign up to set email alerts
|

A Polyamine-Deficient Diet Prevents Oxaliplatin-Induced Acute Cold and Mechanical Hypersensitivity in Rats

Abstract: BackgroundOxaliplatin is an anticancer drug used for the treatment of advanced colorectal cancer, but it can also cause painful peripheral neuropathies. The pathophysiology of these neuropathies has not been yet fully elucidated, but may involve spinal N-methyl-D-aspartate (NMDA) receptors, particularly the NR2B subunit. As polyamines are positive modulators of NMDA-NR2B receptors and mainly originate from dietary intake, the modulation of polyamines intake could represent an interesting way to prevent/modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 43 publications
(54 reference statements)
1
34
0
Order By: Relevance
“…At physiological pH, polyamine can positively modulate NMDAR function by inhibiting GluN1-GluN2B channel function [56; 71]. Decreasing the polyamine levels in the diet can ameliorate hyperalgesic status by decreasing glutamate levels in the spinal cord [14] and potentiate the analgesic effect of morphine [59]. Using models of hyperalgesia (inflammatory, post-incision, neuropathic, OIH, and non-nociceptive environmental stress), Rivat and colleagues showed that a polyamine-deficient diet prevented phosphorylation on tyrosine residues of the GluN2B subunit and inhibited the appearance of hyperalgesia [59].…”
Section: Discussionmentioning
confidence: 99%
“…At physiological pH, polyamine can positively modulate NMDAR function by inhibiting GluN1-GluN2B channel function [56; 71]. Decreasing the polyamine levels in the diet can ameliorate hyperalgesic status by decreasing glutamate levels in the spinal cord [14] and potentiate the analgesic effect of morphine [59]. Using models of hyperalgesia (inflammatory, post-incision, neuropathic, OIH, and non-nociceptive environmental stress), Rivat and colleagues showed that a polyamine-deficient diet prevented phosphorylation on tyrosine residues of the GluN2B subunit and inhibited the appearance of hyperalgesia [59].…”
Section: Discussionmentioning
confidence: 99%
“…It could therefore be relevant to further investigate acupuncture treatments, as such traditional medicine might offer patients a drug-free coping mechanism for neuropathic pain. Lastly, animal studies have provided insight into other factors/supplements which could be worth studying in CRC patients, such as curcumin, flavonoids, reduced poly-amine diets, and vitamin C, all of which have been found to decrease CIPN in mice models [6468]. …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this polyamine-deficient diet totally prevented cold and mechanical allodynia in animal models of acute oxaliplatin-induced peripheral neuropathy. Moreover, this polyamine-deficient diet suppressed the increase of the spinal glutamate concentration found in neuropathic rats subjected to pain [80]. A clinical trial is ongoing and assessing the preventive effect of a polyamine-depleted diet on oxaliplatin-induced peripheral neuropathy (Table 5).…”
Section: Glutamate-related Strategiesmentioning
confidence: 99%